pH-driven enhancement of anti-tubercular drug loading on iron oxide nanoparticles for drug delivery in macrophages - Cotta, Karishma Berta; Mehra, Sarika; Bandyopadhyaya, Rajdip (Beilstein Journal of Nanotechnology, 2021)
Nanoparticle deployment in drug delivery is contingent upon controlled drug loading and a desired release profile, with simultaneous biocompatibility and cellular targeting. Iron oxide nanoparticles (IONPs), being biocompatible, are used as drug carriers. However, to prevent aggregation of bare IONPs, they are coated with stabilizing agents. We hypothesize that, zwitterionic drugs like norfloxacin (NOR, a fluoroquinolone) can manifest dual functionality – nanoparticle stabilization and antibiotic activity, eliminating the need of a separate stabilizing agent. Since these drugs have different charges, depending on the surrounding pH, drug loading enhancement could be pH dependent. Hence, upon synthesizing IONPs, they were coated with NOR, either at pH 5 (predominantly as cationic, NOR+) or at pH 10 (predominantly as anionic, NOR−). We observed that, drug loading at pH 5 exceeded that at pH 10 by 4.7–5.7 times. Furthermore, only the former (pH 5 system) exhibited a desirable slower drug release profile, compared to the free drug. NOR-coated IONPs also enable a 22 times higher drug accumulation in macrophages, compared to identical extracellular concentrations of the free drug. Thus, lowering the drug coating pH to 5 imparts multiple benefits – improved IONP stability, enhanced drug coating, higher drug uptake in macrophages at reduced toxicity and slower drug release.
Keywords: drug-nanoparticle interactions; drug uptake; intra-macrophage; iron oxide nanoparticles; norfloxacin